Recent Experiences with Surges in Capital Inflows - Kahn, Robert (Occasional Papers; Occasional Paper ;, 1993)
This paper explores the experience of six countries (Chile, Colombia, Egypt, Mexico, Spain and Thailand) with capital inflows. It illustrates that although capital inflows are usually beneficial, too great an inflow can become a problem and make it difficult for authorities to choose the appropriate policy response.